All-sky search for long-duration gravitational wave transients in the first Advanced LIGO observing run - Abbott, B. P. (2018)
We present the results of a search for long-duration gravitational wave transients in the data of the LIGO Hanford and LIGO Livingston second generation detectors between September 2015 and January 2016, with a total observational time of 49 d. The search targets gravitational wave transients of 10-500 s duration in a frequency band of 24-2048 Hz, with minimal assumptions about the signal waveform, polarization, source direction, or time of occurrence. No significant events were observed. As a result we set 90% confidence upper limits on the rate of long-duration gravitational wave transients for different types of gravitational wave signals. We also show that the search is sensitive to sources in the Galaxy emitting at least similar to 10-8 M(circle dot)c(2) in gravitational waves.